The potential of pineapple peel flour (Ananas comosus) in controlling Aeromonas hydrophila infection in sangkuriang catfish (Clarias gariepinus) - Sari, Ita; Agustina, Agustina; Ricko Reynalta (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
Hematological conditions can reflect the health status of fish. This study aimed to analyze the effect of adding different doses of pineapple peel flour to feed on clinical symptoms, anatomical pathology, survival rate, hematological parameters, and cellular immunity of Sangkuriang catfish after infection with Aeromonas hydrophila. The study was conducted using a Completely Randomized Design (CRD) with four treatments and three replications. The treatments consisted of feed supplemented with 0%, 10%, 20%, and 30% pineapple peel flour. The results showed that different doses of pineapple peel flour in feed had a significant effect (P<0.05) on anatomical pathology, survival rate, hematocrit levels, total erythrocytes, total leukocytes, and the percentage of lymphocytes, monocytes, and neutrophils in Sangkuriang catfish after A. hydrophila infection. The findings also indicated that the 20% dose of pineapple peel flour in feed was the most effective in controlling A. hydrophila infection.